Numerical simulation of pushover tests on a model jack-up platform on clay - Vlahos, G; Cassidy, M; Martin, C (2011)
This paper assesses a method for predicting the ultimate capacity and failure mode of a model jack-up platform subjected to monotonic pushover tests on soft clay. Separate structural and geotechnical analyses are incapable of making such predictions, so in this work integrated structural/geotechnical simulations are evaluated against detailed experimental pushover data. The commercial finite-element program Abaqus is used, with standard beam elements representing the jack-up structure and a user-defined element describing the behaviour of each spudcan footing by means of a force-resultant plasticity model. This model takes a macro-element approach by expressing the foundation behaviour purely in terms of the loads on the spudcan and the corresponding displacements. Although the model has proven ability to simulate the single-footing experiments from which it was derived, the load paths experienced by the spudcans of a three-legged jack-up are significantly different. To investigate this, numerical simulations of three experimental pushover tests on a 1:250 scale model jack-up have been performed. The tests represent jack-ups with different leg lengths and load orientations. The integrated numerical modelling approach successfully predicts three different failure modes, although the predictions of ultimate pushover capacity are consistently conservative. Because previously published parameters were used for the foundation model, these predictions demonstrate the versatility of the spudcan model in the context of a multi-footing structure, and confirm the effectiveness of the integrated analysis technique.